Effect of Allogeneic Platelet Lysate and Cyanoacrylate Tissue Glue on the Fibrovascularization of the Porous Polyethylene Implant. Issue 1 (January 2016) - Ozturk, Sinan; Sahin, Cihan; Tas, Arzu Caputcu; Muftuoglu, Tuba; Karagoz, Huseyin
Abstract : Abstract: Because of limited autogenous tissue sources, donor site morbidity, and difficulty of shaping the autologous tissue, surgeons often need to use alloplastic frameworks in reconstruction of 3-dimensional tissue defects. Synthetic porous polyethylene (PP) implant is widely used in plastic surgery for 3-dimensional reconstruction of the lost or highly deformed tissues. One of the main factors of PP implant exposure is delayed fibrovascular ingrowth. In the present study, the authors investigated the effect allogeneic plateletlysate (PL) and cyanoacrylate tissue glue (CTG) (2-octyl cyanoacrylate) on the fibrovascularization of the PP implant. Twenty adult female Wistar rats were divided into 4 groups equally, according to the different surgical techniques and implanted materials used. Only PP implant was implanted subcutaneously through a skin incision on the chest wall skin of the rats in the control group; however, CTG was applied with PP implant in the cyanoacrylate group, PL was applied with PP implant in the platelet group, CTG and platelet was applied together with PP implant in the combination group. All of the implants in each group were histologically assessed at postoperative second week. Determination of the collagen density in the tissues, inflammation, and necrosis and vascularization status was assessed semiquantitatively. A denser collagen structure, low inflammation, and necrosis were found in PL groups. There was, however, a significant decrease in vascular density with PL-treated groups. PL treatment may have a potential to reduce complications related to PP implants.